Prism adaptation alters spatial remapping in healthy individuals: Evidence from double-step saccades - Bultitude, J; Van der Stigchel, S; Nijboer, T (2013)
The visual system is able to represent and integrate large amounts of information as we move our gaze across a scene. This process, called spatial remapping, enables the construction of a stable representation of our visual environment despite constantly changing retinal images. Converging evidence implicates the parietal lobes in this process, with the right hemisphere having a dominant role. Indeed, lesions to the right parietal lobe (e.g., leading to hemispatial neglect) frequently result in deficits in spatial remapping. Research has demonstrated that recalibrating visual, proprioceptive and motor reference frames using prism adaptation ameliorates neglect symptoms and induces neglect-like performance in healthy people - one example of the capacity for rapid neural plasticity in response to new sensory demands. Because of the influence of prism adaptation on parietal functions, the present research investigates whether prism adaptation alters spatial remapping in healthy individuals. To this end twenty-eight undergraduates completed blocks of a double-step saccade (DSS) task after sham adaptation and adaptation to leftward- or rightward-shifting prisms. The results were consistent with an impairment in spatial remapping for left visual field targets following adaptation to leftward-shifting prisms. These results suggest that temporarily realigning spatial representations using sensory-motor adaptation alters right-hemisphere remapping processes in healthy individuals. The implications for the possible mechanisms of the amelioration of hemispatial neglect after prism adaptation are discussed. © 2012 Elsevier Ltd.